STUDY ON THE PHYSICOCHEMICAL AND CHEMICAL PARAMETERS OF DRINKING AND SURFACE WATERS FROM MINE AREA AT VILLAGE BOV, BALKAN MOUNTAIN, BULGARIA - MLADENOV, Metodi; KARADJOVA, Irina; GENTSCHEVA, Galia; PREDOEVA, Albena (Studia Universitatis Babeș-Bolyai Chemia, 2018)
Water quality is influenced by natural local climate, geology and anthropogenic effects. In the present study, surface waters in hydrographic areas situated in a mining region, in the vicinity of an abandoned copper mine, are characterized and their quality assessed from the viewpoint of the requirements of the European Water Frame Directive and Drinking Water Directive. Three sampling campaigns starting in 2012, from 16 sampling sites, performed in different seasons, in order to evaluate both natural, seasonal variations connected with water regimes and anthropogenic pressures. Chemical elements (Al, As, Ba, Cd, Cr, Co, Cu, Fe, Hg, Mn, Ni, Pb, Se, U, V, Zn and lanthanides) and physicochemical parameters (pH, conductivity, hardness, chemical oxygen demand (CODKMnO4); biological oxygen demand (BOD5); dissolved oxygen; dissolved solids; suspended matter; dry residue; chlorides; sulphates; nitrates; phosphates) were measured for characterization and evaluation of different water sources in the region. Conclusions for the further use of waters from this region as tap waters were presented and validated through the determination of much more chemical elements than these required from national legislation.